2015
DOI: 10.1007/s00330-015-3978-7
|View full text |Cite
|
Sign up to set email alerts
|

Coronary calcium screening with dual-source CT: reliability of ungated, high-pitch chest CT in comparison with dedicated calcium-scoring CT

Abstract: • CAC is an independent risk factor for major cardiac events. • ECG-gated techniques are the reference standard for calcium scoring. • Great interest is directed toward calcium scoring on non-gated chest CT examinations. • Reliable calcium scoring can be obtained with dual-source CT in a high-pitch mode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 26 publications
3
27
0
1
Order By: Relevance
“…Prior results have shown good correlation of the calcium score on non-gated CT compared to dedicated ECG gated calcium CT scoring 2, 20 . Although a high calcium score is predictive of coronary artery disease, the calcium score is understood as a marker of disease, rather than direct visualization of coronary stenosis.…”
Section: Discussionmentioning
confidence: 95%
“…Prior results have shown good correlation of the calcium score on non-gated CT compared to dedicated ECG gated calcium CT scoring 2, 20 . Although a high calcium score is predictive of coronary artery disease, the calcium score is understood as a marker of disease, rather than direct visualization of coronary stenosis.…”
Section: Discussionmentioning
confidence: 95%
“…However, recent studies have shown a strong correlation between gated and nongated scans, and CAC measured on nongated scans has been shown to be independently associated with clinical outcomes. 11,31,32 It is possible that some events were not captured on follow-up, but this bias would likely affect both scores equally because the scores were estimated in the same participants. The study also has a number of strengths.…”
Section: Discussionmentioning
confidence: 99%
“…Findings were similar in the National Lung Screening Trial (NLST) of 1575 CT scans [16]. In another study, the sensitivity and specificity of routine chest CT scanning for detecting positive CAC scores were 96.4 % and 100 %, respectively [17]. Nonetheless, the use of CAC in assessing cardiac risk in cancer patients having undergone cancer therapy, is unknown.…”
Section: Introductionmentioning
confidence: 77%